Whole-genome sequencing of Neisseria gonorrhoeae in a forensic transmission case. (September 2019) - Francés-Cuesta, Carlos; de la Caba, Idoia; Idigoras, Pedro; Fernández-Rodríguez, Amparo; del Valle Pérez, David; Marimón, Jose Maria; González-Candelas, Fernando
Highlights: Potential case of sexual abuse of a child with transmission of gonorrhoeae. Isolates cultured from suspect, victim and two local controls. PFGE and MLST analyses were not discriminatory enough. Whole genome sequencing (WGS) revealed complete identity between suspect and victim. First published case of bacterial WGS analysis used in court as evidence for child abuse. Abstract: Molecular epidemiology and phylogenetic analyses are frequently used in the investigation of viral transmission cases in forensic contexts. Here, we present the methods and results of the analysis of a bacterial transmission episode in an alleged child abuse case using complete genome sequences obtained by high-throughput sequencing (HTS) methods. We obtained genomes of Neisseria gonorrhoeae from the victim, the suspect, and 29 unrelated controls. The analysis of the genomes revealed that the victim and suspect isolates had identical sequences in both the bacterial chromosome and the single plasmid present in them. One of the local controls was very similar (differing in only 2 SNPs) to the case sequences, but the remaining controls were very divergent. Additional cases of identity and very high similarity among controls were observed occasionally, pointing at recent transmission cases. These results were more discriminative than the previous molecular epidemiology analyses performed at the hospital's Microbiology Service, as Multi-Locus Sequence Typing (MLST) could not distinguish between the suspect/victim and the controls isolates, and Pulse Field Gel Electrophoresis (PFGE) was not able to distinguish between the suspect/victim and one of the local controls. These results lead us to conclude that complete bacterial genome sequences obtained with HTS technologies may be a valuable tool for establishing recent transmission cases and, although more studies are needed, they have a great potential for being used in forensic analyses.